Strategic Digital Integration: Unravelling the Impact of Social Media, Data Analytics, and Branding on Sustainable Marketing Strategies and Consumer Engagement in the Tourism Industry in Bali Province - Sudrajat, Arief (IJBLE Scientific Publications Community Inc., 2024)
This study examines the complex dynamics of digital integration in Bali's travel and tourist sector, with a particular emphasis on the effects of branding, social media, and data analytics on customer engagement and sustainable marketing tactics. 355 different enterprises in the province responded to a quantitative analysis that was carried out. The structural model analysis validated all of the proposed hypotheses, while the measurement model assessment confirmed the constructs' validity and reliability. The findings highlight the beneficial connections between consumer involvement, branding tactics, data analytics adoption, social media integration, and sustainable marketing techniques. The study's conclusions can be trusted because the model fit indices show a respectable fit. This research highlights the strategic significance of digital integration for sustainability and customer connections, providing useful insights for companies trying to navigate Bali's tourism sector in the digital era.